COVID-19 pandemic times: depressive symptomatology in the elderly (Research, Society and Development, 2021)
Introduction: Currently, the world population continues to face the Pandemic of COVID-19. The social distancing and the possibility of getting sick can bring new suffering to people, such as depression, especially for the elderly. Objective: To evaluate the depressive symptoms of older people during the COVID-19 pandemic. Methodology: This research is characterized as being transversal, descriptive and exploratory, with a quantitative approach. Data collection was performed online through a form, which contained the following instruments: sociodemographic and clinical questionnaire and the Geriatric Depression Scale – GDS. Forty-four elderly people with ages ranging from 60 to 87 years participated in a non-probabilistic way for convenience. Regarding data analysis, a database was created with the previous coding of responses, using the Statistical Package for Social Science (SPSS) software for Windows, version 20, and R program version 3.5.1. Results: The sociodemographic profile of the participants was mainly composed of elderly females who declared themselves Catholic. Furthermore, most participants were from the Northeast, retired, married, with a low level of education and monthly family income between 1 and 2 minimum wages. We found that 75% of the elderly did not have depression, while 25% had moderate or severe depressive symptoms. Concluding remarks: Given this, it is possible to understand that isolation and social distancing, although necessary during the COVID-19 pandemic, can have harmful effects on the mental health of the elderly.